Inter-coat protein loading of active ingredients into Tobacco mild green mosaic virus through partial dissociation and reassembly of the virion - Ivonne González-Gamboa; Adam A. Caparco; Justin McCaskill; Paulina Fuenlabrada-Velázquez; Samuel S. Hays; Zhicheng Jin; Jesse V. Jokerst; Jonathan K. Pokorski; Nicole F. Steinmetz (Scientific Reports, 2024)
Abstract Chemical pesticide delivery is a fundamental aspect of agriculture. However, the extensive use of pesticides severely endangers the ecosystem because they accumulate on crops, in soil, as well as in drinking and groundwater. New frontiers in nano-engineering have opened the door for precision agriculture. We introduced Tobacco mild green mosaic virus (TMGMV) as a viable delivery platform with a high aspect ratio and favorable soil mobility. In this work, we assess the use of TMGMV as a chemical nanocarrier for agriculturally relevant cargo. While plant viruses are usually portrayed as rigid/solid structures, these are “dynamic materials,” and they “breathe” in solution in response to careful adjustment of pH or bathing media [e.g., addition of solvent such as dimethyl sulfoxide (DMSO)]. Through this process, coat proteins (CPs) partially dissociate leading to swelling of the nucleoprotein complexes—allowing for the infusion of active ingredients (AI), such as pesticides [e.g., fluopyram (FLP), clothianidin (CTD), rifampicin (RIF), and ivermectin (IVM)] into the macromolecular structure. We developed a “breathing” method that facilitates inter-coat protein cargo loading, resulting in up to  ~ 1000 AIs per virion. This is of significance since in the agricultural setting, there is a need to develop nanoparticle delivery strategies where the AI is not chemically altered, consequently avoiding the need for regulatory and registration processes of new compounds. This work highlights the potential of TMGMV as a pesticide nanocarrier in precision farming applications; the developed methods likely would be applicable to other protein-based nanoparticle systems.